Morphine Suppresses Liver Cancer Cell Tumor Properties In Vitro and In Vivo - Zhang, Hao-Wen; Wang, Fei; Zhou, Ya-Qun; Xu, San-Ping; Yu, Shi-Ying; Zhang, Zhan-Guo (Frontiers in Oncology, 2021)
Morphine is an analgesic widely adopted to relieve cancer pain. A number of discrepancies, however, are presented by the published literature, with reports suggesting that opioids may either promote or inhibit the spread of cancer. It is of great significance to determine whether morphine may increase the risk of metastasis while utilized in liver cancer surgical treatment. In this study, we explore the effects of morphine on liver cancer cells in vitro and in vivo. Our results showed that morphine does not promote proliferative ability to cultured liver cancer cells. While morphine could increase the apoptosis rate of Hep3B/HepG2 cells. Furthermore, morphine could significantly inhibit the migratory and invasion ability of Hep3B/HepG2 cells. Subsequent investigations disclosed that morphine could inhibit sphere formation ability of Hep3B/HepG2 cells by using sphere formation assay. Based on nude mouse models, we demonstrated that morphine significantly reduced pulmonary tumorigenicity of Hep3B/HepG2 cells. In conclusion, our results found that morphine at clinical concentrations could suppress liver cancer cell tumor properties in vitro and in vivo, indicating the safety of morphine utilization in HCC patients' pain management.